Особливості добровільної відмови пособника від вчинення злочину - Цибулін, Т.; Tsybulin, T. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджуються визначені законодавством умови добровільної відмови пособника від вчинення злочину у співвідношенні з умовами добровільної відмови інших співучасників. Добровільна відмова пособника, як і інших співучасників злочину, має полягати у руйнуванні причинного зв’язку між власними діями та наслідками, тобто перешкоджанні вчиненню злочину іншими співучасниками. Запропоновано шляхи розуміння законодавчих умов добровільної відмови пособника залежно від способів сприяння вчиненню та приховуванню злочину. In the article the conditions of voluntary refusal of the abettor of crime commission determined by the legislation in relation to conditions of voluntary refusal of other accomplices have been investigated. Ways of understanding of legislative conditions of voluntary refusal of the accomplice depending on ways of assistance to commission and concealment of a crime have been offered. If the accomplice carried out intellectual complicity (giving advice, instructions how to commit a crime or contribution to concealment of a crime) beforehand, voluntary refusal can be carried out either by prevention of crime commission, or by the prior notification of public authorities of the prepared crime or the crime which is being committed. If the accomplice has to carry out physical complicity in a type of providing with means or tools of crime commission or to eliminate obstacles, except the prior notification of the mentioned bodies, voluntary refusal can also consist in not commission of such ways of assistance to a crime.
Peculiarities of Voluntary Refusal of the Accomplice to Commit a Crime
Keywords: добровільна відмова; співучасть; пособник; співвиконавець; фізичне пособництво; інтелектуальне пособництво; voluntary refusal; complicity; accomplice; abettor; physical complicity; intellectual complicity